Clown and Silver Man Construction by the Social and Community Empowerment Service of Gorontalo City - Yusdin D. Turangan; Ellys Rachman; Misbahudin Djaba; Dandy Okorontah (Walidem Institute and Publishing, 2026)
Objective: This study aims to identify and analyze the coaching process carried out by the Gorontalo City Social and Community Empowerment Service for street clowns and silver men, as well as evaluate the level of effectiveness of the implementation of the program. Theoretical framework: The theoretical framework of this research is based on the theory of social development, community empowerment, and social control theory that emphasizes the urgency of rehabilitation, the provision of skills training programs, and the strengthening of cross-sector coordination to overcome complex and sustainable social problems. Literature review: The literature review in this study examines the phenomenon of the emergence of beggars with creative methods, namely street clowns and silver men, which represent a new form of begging practice in public spaces. In addition, the literature also emphasizes the role of local governments in the implementation of social development programs, the urgency of the involvement of officials in supervision, and the effectiveness of community empowerment programs in suppressing similar practices. Method: This study uses a qualitative approach with a descriptive method. Data collection techniques include observation, in-depth interviews, and literature studies. The research analysis focused on three main indicators, namely the existence of coaching programs, the availability of apparatus, and supervision mechanisms. Results: The results of the study show that the implementation of coaching has not reached the expected effectiveness. The main obstacles include the absence of post-coaching skills training programs, the limited number of officers on duty, and weak coordination between related agencies. This has resulted in the return of most street clowns and silvermen to their old activities on the streets, even with a tendency to move to areas with looser levels of surveillance. Implications: This study emphasizes the urgency of strengthening sustainable social development programs through skills training, increasing the number of officials, and cross-sectoral coordination. These findings can be a reference for local governments in formulating policies to handle social problems more effectively. Novelty: The novelty of this research lies in the study of the contemporary phenomenon of beggars with a new identity, namely, street clowns and silver men. This research also provides a critical analysis of the limitations of local government development programs to enrich academic studies as well as provide practical input for social policies.